ANALISIS PERAN STRATEGI PEMASARAN GLOBAL DAN MANAJEMEN RITEL DIGITAL TERHADAP KEPUASAN NASABAH PADA PT AGRODANA FUTURES - Ahnaf, Muhammad; Zawawi, Zawawi (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to thoroughly examine the role of global marketing strategies and digital retail management in enhancing customer satisfaction at PT Agrodana Futures. In the context of a rapidly evolving financial services industry, marked by intense global competition, companies are required to integrate cross-border marketing approaches with efficient, technology-based service systems that are responsive to the needs of modern customers. This research focuses on how the synergy between global marketing strategies and digital service transformation can generate added value, improve interaction quality, and increase overall customer satisfaction. The research employs a descriptive approach, utilizing data collection techniques including direct observation, semi-structured interviews, and documentation. These techniques were chosen to gather in-depth contextual information from both internal company operations and the real experiences of customers and management involved in the marketing and service delivery process. The core of the study explores how the integration of cross-national marketing initiatives with digital service systems affects customer perception, enhances information accessibility, and strengthens long-term customer relationships. The findings reveal that adaptive global marketing strategies, when combined with responsive and digitally integrated service management, have a positive and significant impact on customer perception, service convenience, and satisfaction levels. These results underscore the importance of aligning strategic marketing with efficient customer service systems as a foundation for building sustainable customer loyalty. This research is expected to provide both conceptual and practical insights for financial service providers in designing relevant, innovative, and customer-oriented strategies in today’s digital and globalized landscape